Population-wide impact of a pragmatic program to identify and manage individuals at high-risk of cardiovascular disease: a cluster randomized trial in 120 villages from Northern China - Chen, Siyu; Yan, Lijing L.; Feng, Xiangxian; Zhang, Jianxin; Zhang, Yuhong; Zhang, Ruijuan; Zhou, Bo; Wu, Yangfeng (Frontiers in Cardiovascular Medicine, 2024)
Objectives: To explore the population-wide impacts of the evidence-based high-risk strategy for prevention of cardiovascular diseases in resource-poor populations.Methods: A cluster randomized controlled trial was conducted among 120 villages in rural China, with 60 on intervention and 60 on usual care as controls, for 2 years. The intervention emphasized training village doctors to identify high-risk individuals and administer standardized treatments focusing on hypertension management. A random sample of 20 men aged ≥50 years and 20 women aged ≥60 years was drawn from each village before randomization for the baseline survey, and another independent random sample with the same age and sex distribution was drawn at 2 years for the post-intervention survey. The primary outcome was the population mean systolic blood pressure (SBP). Secondary outcomes included the proportions of patients who received regular primary care, antihypertensive medications, aspirin, or lifestyle advice.Results: A total of 5654 high cardiovascular risk individuals were identified and managed by village doctors in intervention villages for 15 months on average, with mean SBP lowered by 19.8 mmHg and the proportion with blood pressure under control increased from 22.1% to 72.7%. The primary analysis of the two independent samples (5050 and 4887 participants each) showed that populationwide mean SBP in intervention villages did not differ from that in control villages at 2 years (mean difference=1.0 mmHg, 95% CI: -2.19, 4.26; P=0.528), though almost all secondary outcomes concerning primary care indicators significantly increased in intervention villages.In our study, the pragmatic cardiovascular risk management program targeting on high-risk individuals significantly improved the quality of primary care. However, its impact on population blood pressure level and the burden of hypertension-related diseases appeared very limited.